2020
DOI: 10.1038/s41557-020-0514-4
|View full text |Cite
|
Sign up to set email alerts
|

Design of a small molecule that stimulates vascular endothelial growth factor A enabled by screening RNA fold–small molecule interactions

Abstract: Vascular endothelial growth factor A (VEGFA) stimulates angiogenesis in human endothelial cells, and increasing its expression is a potential treatment for heart failure. Here, we report the design of a small molecule (TGP-377) that specifically and potently enhances VEGFA expression by the targeting of a non-coding microRNA that regulates its expression. A selection-based screen, named two-dimensional combinatorial screening, revealed preferences in small-molecule chemotypes that bind RNA and preferences in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
52
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 50 publications
(58 citation statements)
references
References 54 publications
4
52
2
Order By: Relevance
“…This work suggested that bioactive RNA-targeted ligands may occupy a focused corner of drug-like chemical space. These results were further supported by recent work from the Disney laboratory in collaboration with AstraZeneca (57). The researchers observed that although the RNA-binding hit compounds were structurally dissimilar to those in R-BIND (113), they still shared the identified physicochemical properties.…”
Section: Rna-biased Librariesmentioning
confidence: 53%
See 2 more Smart Citations
“…This work suggested that bioactive RNA-targeted ligands may occupy a focused corner of drug-like chemical space. These results were further supported by recent work from the Disney laboratory in collaboration with AstraZeneca (57). The researchers observed that although the RNA-binding hit compounds were structurally dissimilar to those in R-BIND (113), they still shared the identified physicochemical properties.…”
Section: Rna-biased Librariesmentioning
confidence: 53%
“…2 ). Using a technique termed two-dimensional combinatorial screening, the Disney laboratory constructed the proposed database, now known as Inforna, which they have used to target several RNAs with small molecules possessing activity in cell culture and/or animal models of cancer and neurological disorders ( 53 , 54 , 55 , 57 , 58 , 59 , 60 ). A key strategy in Disney's work has been that of modular assembly, where at least two binding moieties are linked together to interact with neighboring secondary structure motifs such as those found in precursor miRNAs and trinucleotide repeat RNAs ( Fig.…”
Section: Framework 1: Rna Secondary Structure Motifs Can Be Used As Mmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to the design of homodimeric molecules, Inforna can be used to design heterodimeric compounds which bind avidly to miRNAs. 49 Vascular endothelial growth factor A (VEGFA) stimulates angiogenesis in human endothelial cells and is a sought after target in the treatment of heart failure. [50][51][52] MiR-377 regulates VEGFA expression, and repression of miR-377 by an antisense oligonucleotide has been shown to rescue VEGFA expression and stimulate angiogenesis.…”
Section: Design Of Dimeric Small Molecules Targeting Disease-causing mentioning
confidence: 99%
“…2F and Table S1, ESI †). 49 Expression levels of miR-377 from human umbilical vein endothelial cells (HUVEC) treated with TGP-377 were knocked down with an IC 50 of B500 nM, 10-fold more potently than the lead small molecule monomer (Table S1, ESI †). Accumulation of pre-miR-377 was also observed, demonstrating TGP-377 acts through inhibition of Dicer processing and correspondingly rescues VEGFA expression.…”
Section: Design Of Dimeric Small Molecules Targeting Disease-causing mentioning
confidence: 99%